Some preliminary notes on the music of the Cwezi cult in Ankole (Western Uganda) - Van Thiel, Paul (International Library of African Music, 1973)
The Rev. Y. B. Bamunoba made a special study of the Cwezi cult in Ankole. In the Uganda Journal, Vol. 29, no. 1 (1965), he published an interesting article in joint authorship with F. B. Welbourn on the emandwa initiation which is still in vogue, though only to a limited extent and usually very locally. Their essay gives a detailed description of the ceremonial followed during the initiation rites and enumerates a few situations in which the emandwa rites are performed. More valuable information on the subject is recorded in another article 'Diviners for the Abagabe' (Uganda Journal, Vol. 29, no. 1). The content of both papers is related to the spirits of the legendary Cwezi rulers. Although incidental mention is made of ritual singing, dancing and flute playing, no further details on the music are given
Keywords: African Music; Uganda; Cwezi Cult; Ankole